Cohort at Risk: Long-Term Consequences of Conflict for Child School Achievement - Hendrik Jürges; Luca Stella; Sameh Hallaq; Alexandra Schwarz (Institute of Labor Economics (IZA), 2017)
We investigate the long-term effects of households' exposure to violent conflict on children's educational attainment in primary school, studying cognitive and non-cognitive skills as possible causal channels. Our identification strategy exploits the locality-level variation in the intensity of the Israeli-Palestinian conflict in the West Bank during the Second Intifada (2000–2005). We show that an increase in family experience of conflict has large negative long-term effects on the educational attainment of children measured by grade point averages. Impaired non-cognitive rather than cognitive skills are identified as channels through which exposure affects children's educational achievement.
Keywords: D10; I20; F51; O12; 330; conflict; schooling; children